2017
DOI: 10.1088/1361-6668/aa6785
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of the toroidal field ITER production conductors

Abstract: The production of the superconducting cables for the toroidal field (TF) magnets of the ITER machine has recently been completed at the manufacturing companies selected during the previous qualification phase. The quality assurance/quality control programs that have been implemented to ensure production uniformity across numerous suppliers include performance tests of several conductor samples from selected unit lengths. The short full-size samples (4 m long) were subjected to DC and AC tests in the SULTAN fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
2
25
2
Order By: Relevance
“…Therefore, it is meaningful to evaluate the margin of improvement for a conductor not only in term of current sharing temperature but rather in term of critical current of Nb 3 Sn strands. A similar analysis was carried out for ITER TF conductors (see figure 10 in [17]) and it was found that, after setting the effective strain at -0.5%, the corresponding critical current was found to be about only 50% of the values expected for uniform strain.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Therefore, it is meaningful to evaluate the margin of improvement for a conductor not only in term of current sharing temperature but rather in term of critical current of Nb 3 Sn strands. A similar analysis was carried out for ITER TF conductors (see figure 10 in [17]) and it was found that, after setting the effective strain at -0.5%, the corresponding critical current was found to be about only 50% of the values expected for uniform strain.…”
Section: Discussionmentioning
confidence: 65%
“…In 2011 [16] the effective strain of the first qualification samples of ITER TF conductors (20 samples) was estimated to be in the range between -0.64% and -0.89% after 1000 electromagnetic cycles. In the 2017 release of values [17] regarding the production conductors (over 50 samples) the initial (after one electromagnetic cycle) effective strain was between -0.60% and -0.90%; after 1000 electromagnetic cycles the range is between -0.62% and -0.98%. Over 70 ITER TF conductors have been measured so far in the SULTAN facility at Swiss Plasma Center; the number of sample as a function of effective strain (data from [16] and [17]) is summarized in figure 1: majority of the conductors have effective strain in the -0.65% to -0.85% range.…”
Section: Strain In Iter Cicmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in the current sharing temperature and n-value of Nb3Sn cables for the ITER TF coils and central solenoid, during electromagnetic and warm-up-cool-down cycling after 1/10 th of the proposed number of cycles that the ITER TF coils will undergo, have been required [6]. Although their performance now meets the specification for ITER [7], residual concerns about the use of brittle Nb3Sn are met by having one spare central solenoid coil and one spare TF coil [8]. Even so, replacing a damaged TF coil is considered a long time-scale and "high difficulty" event [9] that currently hinders commercialization of fusion energy.…”
Section: Introductionmentioning
confidence: 99%